2020
DOI: 10.3390/antiox9111107
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Chronic Inflammation with Withanolide Phytochemicals—A Withaferin A Perspective

Abstract: Chronic inflammatory diseases are considered to be one of the biggest threats to human health. Most prescribed pharmaceutical drugs aiming to treat these diseases are characterized by side-effects and negatively affect therapy adherence. Finding alternative treatment strategies to tackle chronic inflammation has therefore been gaining interest over the last few decades. In this context, Withaferin A (WA), a natural bioactive compound isolated from Withania somnifera, has been identified as a promising anti-can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 139 publications
(90 reference statements)
1
26
0
Order By: Relevance
“…Additionally, reduced expression of STAT and JAK, and increased expression of IKBKG and IKBKB have been observed ( Figure 2 ) [ 162 ]. By targeting critical inflammatory pathways like NF-κB and nuclear factor erythroid 2 related factors 2 signaling, WA defeats inflammatory disease in numerous in vitro and preclinical in vivo models of neurodegenerative disorders like AD and PD, cystic fibrosis, and osteoarthritis ( Table 1 ) [ 20 ].…”
Section: Therapeutic Implications Of Wa In Admentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, reduced expression of STAT and JAK, and increased expression of IKBKG and IKBKB have been observed ( Figure 2 ) [ 162 ]. By targeting critical inflammatory pathways like NF-κB and nuclear factor erythroid 2 related factors 2 signaling, WA defeats inflammatory disease in numerous in vitro and preclinical in vivo models of neurodegenerative disorders like AD and PD, cystic fibrosis, and osteoarthritis ( Table 1 ) [ 20 ].…”
Section: Therapeutic Implications Of Wa In Admentioning
confidence: 99%
“…Among these mechanisms is in silico analysis, which has shown a solid probable intermolecular interaction between WA and IKKγ that interrupts the development of the IKK complex and inhibits IκB depletion [ 171 ]. Another suggested mechanism of WA-mediated inhibition of NF-κB is by straight interaction of WA with NF-κB itself [ 172 ] or its IκB inhibitor [ 20 , 172 ]. Thus, it was concluded that pure WA has important NF-κB inhibitor activity, which makes it a novel anti-inflammatory agent for the treatment of AD [ 163 ].…”
Section: Therapeutic Implications Of Wa In Admentioning
confidence: 99%
See 1 more Smart Citation
“…The present study follows up on prior work from this group that has been investigating the role of NFκB signaling in the pathogenesis of amyotrophic lateral sclerosis [4][5][6]. One of the activities that has been credited to WFA is to inhibit NFκB signaling to reduce neuroinflammation (reviewed in [7]). In prior work, TDP43 with mutations associated with amyotrophic lateral sclerosis and frontotemporal dementia was shown to interact with NFκB and aberrantly activate neuroinflammatory pathways [5].…”
mentioning
confidence: 98%
“…Withaferin A (WFA), an archetype withanolide, discovered from the root extract of Withania somnifera , is well known for immunomodulatory properties (8). Little is known about the effect of this compound on T-lymphocyte migration.…”
mentioning
confidence: 99%